Characterization of ancestry informative markers in the Tigray population of Ethiopia: A contribution to the identification process of dead migrants in the Mediterranean Sea. (March 2020) - Kumar, H.R.S.; Haddish, K.; Lacerenza, D.; Aneli, S.; Di Gaetano, C.; Tewelemedhin, G.; Manukonda, R.V.; Futwi, N.; Alvarez-Iglesias, V.; de la Puente, M.; Fondevila, M.; Lareu, M.V.; et al.
Highlights: A Tigray (Ethiopia) population sample was typed with 46 AIM-indel and 31 AIM-SNPs. A ∼50 % non-African genetic component was seen in Tigray by STRUCTURE analysis. AIMs provide differentiation between Tigray and other sub-Saharan African populations. Limited differentiation was possible between Tigray and Middle Eastern populations. A reference AIMs dataset can help the identification of Eastern African dead migrants. Abstract: Determination of bio-geographical ancestry by means of DNA ancestry informative markers (AIMs) can contribute to the identification of human remains in missing person cases and mass disasters. While the presence of Eastern Africans among the migrant victims of trafficking accidents in the Mediterranean Sea is often suspected, few studies have addressed the ability of autosomal AIM panels in current use in forensic laboratories to provide differentiation of populations within the African continent. In this study, two assays consisting of 46 AIM-Indels and 31 AIM-SNPs were typed in a Tigray population sample from Northern Ethiopia. STRUCTURE analysis showed that the Tigray population is characterized by a strong (∼50 %) non-African genetic component shared with European and Middle Eastern populations. The intermediate position of the Tigray sample between sub-Saharan African and European / Middle Eastern reference population samples was confirmed by principal component analysis. Both AIM panels provided effective differentiation between Tigray and sub-Saharan African populations. Classification accuracy of other populations involved in the current Mediterranean migrant crisis, like South Asians, was superior with the AIM-SNP panel compared to the AIM-Indel panel. Misclassification of Middle Eastern samples as Tigray was frequent with both AIM-indel (∼30 % misclassified) and AIM-SNPs (∼20 %). However, with AIM-SNPs, error rates were reduced to acceptable levels by applying cautionary minimum thresholds to assignment likelihoods. Establishment of an Eastern African reference database of AIMs that can be genotyped by means of low cost, small-scale assays compatible with capillary electrophoresis, sets a balance between the need for ancestry inference tools and the budget limitations faced by Italian laboratories engaged in the humanitarian identification of dead migrants recovered from the Mediterranean Sea.